Effects of Silica Coating by Physical Vapor Deposition and Repeated Firing on the Low-Temperature Degradation and Flexural Strength of a Zirconia Ceramic - (:unkn) unknown (WILEY, 2019)
Purpose To examine the application of physical vapor deposition (PVD) silica coating as an approach to retard low temperature degradation (LTD) for dental applications. Accelerated aging characteristics of heat- and surface-treated zirconia material were also investigated by exposing specimens to hydrothermal treatment. Materials and Methods The specimens (90 disc-shaped specimens [15 mm x1.2 mm]) were divided into 9 groups (n = 10) according to the test protocol: Ctrl, control (no surface treatment); Ag, autoclave aging; GrAg, grinding + aging; SiAg, silica coating + aging; GrSiAg, grinding + silica coating + aging; 3FAg, 3-time firing + aging; Gr3FAg, grinding + 3-time firing + aging; 5FAg, 5-time firing + aging; Gr5FAg, grinding + 5-time firing + aging. Accelerated aging was performed in a steam autoclave (134 degrees C, 2 bars) for 12 hours. Following each treatment protocol, X-ray diffraction (XRD) analysis was used to estimate the relative amount of monoclinic phase and corresponding transformed zone depth (TZD). Additionally, a biaxial flexure test was used to calculate the flexural strength. Statistical analysis was conducted with one-way ANOVA and Fisher's LSD test (p < 0.05). Results The tetragonal-to-monoclinic transformation was retarded by PVD silica coating only on ground surfaces. Ground and heat-treated specimens exhibited the lowest monoclinic content after aging. The biaxial flexural strength value of the GrAg group was significantly higher than the values in all of the other groups except the SiAg group. The flexural strength value of the GrSiAg group was significantly higher than that of the 3FAg group. There was no statistically significant difference between the other groups (p > 0.05). Conclusions Grinding decreased the susceptibility of zirconia to LTD and increased the flexural strength. PVD silica coating and repeated firing decreased the monoclinic content only in ground specimens during aging.
Keywords: Grinding; heat treatment; hydrothermal aging; silica; strength; zirconia; AIR-PARTICLE ABRASION; Y-TZP ZIRCONIA; MECHANICAL-PROPERTIES; PHASE-TRANSFORMATION; SURFACE TREATMENTS; HYDROTHERMAL DEGRADATION; STABILIZED ZIRCONIA; FRACTURE STRENGTH; HEAT-TREATMENT; MICROSTRUCTURE